Microglia Specific Drug Targeting Using Natural Products for the Regulation of Redox Imbalance in Neurodegeneration - Maurya, Shashank Kumar; Bhattacharya, Neetu; Mishra, Suman; Bhattacharya, Amit; Banerjee, Pratibha; Senapati, Sabyasachi; Mishra, Rajnikant (Frontiers in Pharmacology, 2021)
Microglia, a type of innate immune cell of the brain, regulates neurogenesis, immunological surveillance, redox imbalance, cognitive and behavioural changes under normal and pathological conditions like Alzheimer’s, Parkinson’s, Multiple sclerosis and traumatic brain injury. Microglia produces a wide variety of cytokines to maintain homeostasis. It also participates in synaptic pruning and regulation of neurons overproduction by phagocytosis of neural precursor cells. The phenotypes of microglia are regulated by the local microenvironment of neurons and astrocytes via interaction with both soluble and membrane-bound mediators. In case of neuron degeneration as observed in acute or chronic neurodegenerative diseases, microglia gets released from the inhibitory effect of neurons and astrocytes, showing activated phenotype either of its dual function. Microglia shows neuroprotective effect by secreting growths factors to heal neurons and clears cell debris through phagocytosis in case of a moderate stimulus. But the same microglia starts releasing pro-inflammatory cytokines like TNF-α, IFN-γ, reactive oxygen species (ROS), and nitric oxide (NO), increasing neuroinflammation and redox imbalance in the brain under chronic signals. Therefore, pharmacological targeting of microglia would be a promising strategy in the regulation of neuroinflammation, redox imbalance and oxidative stress in neurodegenerative diseases. Some studies present potentials of natural products like curcumin, resveratrol, cannabidiol, ginsenosides, flavonoids and sulforaphane to suppress activation of microglia. These natural products have also been proposed as effective therapeutics to regulate the progression of neurodegenerative diseases. The present review article intends to explain the molecular mechanisms and functions of microglia and molecular dynamics of microglia specific genes and proteins like Iba1 and Tmem119 in neurodegeneration. The possible interventions by curcumin, resveratrol, cannabidiol, ginsenosides, flavonoids and sulforaphane on microglia specific protein Iba1 suggest possibility of natural products mediated regulation of microglia phenotypes and its functions to control redox imbalance and neuroinflammation in management of Alzheimer’s, Parkinson’s and Multiple Sclerosis for microglia-mediated therapeutics.